Highly Discriminative Genotyping of Mycobacterium abscessus Complex Using a Set of Variable Number Tandem Repeats in China - Huang, Lihua; Li, Haoran; Ren, Weicong; Zhang, Xuxia; Shang, Yuanyuan; Liu, Yi; Liu, Aimei; Pang, Yu (Frontiers in Microbiology, 2022)
In the study, our aim was to comparatively analyze the power of variable number tandem repeat (VNTR) typing to discriminate isolates within these subspecies and to identify potential genetic marker for better molecular typing of Mycobacterium abscessus complex (MABC) strains. A total of 103 clinical MABC isolates were collected from a nationwide cross-sectional study in China. Eighteen VNTR loci were chosen to genotype the MABC isolates. Out of the 103 clinical MABC isolates, there were 76 (73.8%) M. abscessus subsp. abscessus (MAA) and 27 (26.2%) M. abscessus subsp. massiliense (MAM) isolates, respectively. Among the patients with MAA lung diseases, the percentage of patients older than 45 years (67.1%) was significantly higher than that among patients with MAM lung diseases (33.3%, aOR [95% CI]:0.36 [0.13-0.98], P=0.046). Fifteen VNTR loci were designated as being “highly discriminant” in our sample, except for TR109. The total of 103 MABC isolates were fully discriminated into 103 unique patterns by 18-locus VNTR set (HGDI=1.000), of which the inclusion of the top 12 loci yielded a comparative HGDI value (HGDI=0.9998). Remarkably, the order of the diversity of the VNTR loci showed significant difference between MAA and MAM isolates. TR137 and TR2, two loci with high diversity index for MAA isolates, only yielded poor discriminatory power for MAM isolates, the h value was 0.0000 and 0.2621, respectively. A detailed analysis of TR137 in combination with the other 17 VNTR loci showed that the TR137-TR2 combination could fully distinguished MAA from MAM isolates. To conclude, our data reveal that MAA is more prone to affect elderly patients. Additionally, the population structure of MABC isolates circulating in China has high diversity. The combined use of TR137 and TR2 locus provides a simple criterion for precise identification of MABC to the subspecies level